Robust extremum seeking for a second order uncertain plant using a sliding mode controller - Solis, Cesar; Clempner, Julio; Poznyak, Alexander S. (Zielona Góra: Uniwersytet Zielonogórski)
This paper suggests a novel continuous-time robust extremum seeking algorithm for an unknown convex function constrained by a dynamical plant with uncertainties. The main idea of the proposed method is to develop a robust closed-loop controller based on sliding modes where the sliding surface takes the trajectory around a zone of the optimal point. We assume that the output of the plant is given by the states and a measure of the function. We show the stability and zone-convergence of the proposed algorithm. In order to validate the proposed method, we present a numerical example.
Keywords: convex optimization; extremum seeking; continuous-time gradient algorithm; dynamical constrained optimization; unknown functions